2019
DOI: 10.1093/cercor/bhz032
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted AMPA Receptor Function upon Genetic- or Antibody-Mediated Loss of Autism-Associated CASPR2

Abstract: Abstract Neuropsychiatric disorders share susceptibility genes, suggesting a common origin. One such gene is CNTNAP2 encoding contactin-associated protein 2 (CASPR2), which harbours mutations associated to autism, schizophrenia, and intellectual disability. Antibodies targeting CASPR2 have also been recently described in patients with several neurological disorders, such as neuromyotonia, Morvan’s syndrome, and limbic encephalitis. Despite the clear implication o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 58 publications
2
46
1
Order By: Relevance
“…Finally, CASPR2-antibodies may also exert their pathogenicity by altering the protein's known function in AMPAR synaptic traffic. A recent study showed significant synaptic loss of AMPARs in cortical neurons incubated with IgG1 and IgG4 CASPR2 antibodies, while in vivo injection of the same antibodies in the mouse visual cortex significantly decreased AMPAR-mediated currents 67 .…”
Section: Mechanisms Underlying Cognitive Impairmentmentioning
confidence: 97%
See 2 more Smart Citations
“…Finally, CASPR2-antibodies may also exert their pathogenicity by altering the protein's known function in AMPAR synaptic traffic. A recent study showed significant synaptic loss of AMPARs in cortical neurons incubated with IgG1 and IgG4 CASPR2 antibodies, while in vivo injection of the same antibodies in the mouse visual cortex significantly decreased AMPAR-mediated currents 67 .…”
Section: Mechanisms Underlying Cognitive Impairmentmentioning
confidence: 97%
“…Components of this figure were created using Servier Medical Art templates, which are licensed under a Creative Commons Attribution 3.0 Unported License; https://smart.servier.com . The shapes of the electrophysiological traces were modelled on data published in 47 , 61 , 147 . …”
Section: Autoimmune Encephalitismentioning
confidence: 99%
See 1 more Smart Citation
“…Injection of a mixture of CASPR2-Abs in mouse visual cortex produced impaired localization of mouse Caspr2 to excitatory synapses and significantly decreased AMPAR-mediated currents in layer 2/3 pyramidal neurons; this implied a dysfunction of glutamatergic transmission in the pathogenesis of CASPR2-Ab encephalitis (52). Future studies should evaluate in parallel the effects of CASPR2-Abs on its partner protein network and on neuronal activity.…”
Section: Passive Transfer Modelsmentioning
confidence: 98%
“…Today, numerous autism-related proteins have been identified and are object of intensive research efforts in order to understand the phenotypic risks for autism. Examples are MeCP2 protein [ 7 ], reelin protein [ 8 ], CASPR2 protein [ 9 ] and CNTNAP2 protein [ 10 ]. Immune activation and prenatal exposure to toxins such as thalidomide and valproic acid have been considered environmental factors contributing to idiopathic ASD [ 11 ].…”
Section: Introductionmentioning
confidence: 99%